Critical Analysis of Rehabilitation Strategies in Modern Physical Therapy - Murdif , Hussain Hassan Al; Sawidan, Hamad Mesfer Mansor Al; Alsharif, Mohammed Hassan; Alfaqir, Mohammed Ahmed Saleh; Alnasser, Nasser Mohsen Yahia; Abya, Hamad Dhafer Al; Alfaqir, Galeb Abdullah; Alharthi, Fahad Ahmed; alrashah, Rizq awadh; Aldossary, Jamilah Jassim A (Journal of Ecohumanism, 2024)
Rehabilitation has gone through massive changes, especially in physical therapy and the needs of patients with different social demands. This paper presents a critique of current and emerging rehabilitation techniques utilized in physical therapy practice, with emphasis on their outcomes, issues, and advancements. Thus, the purpose of this study is to identify the current practices in the field of stroke rehabilitation, to consider the possible new technologies and methods, to contribute to understanding the evidence-based practices in the rehabilitation field, and to provide an impulse for further research. The study emphasizes the need to address patients as unique individuals and combine the efforts of various professionals, as well as the effective use of digital resources, in order to enhance the results of individuals' treatment processes.